ON THE IMPORTANCE OF FOUR CS IN SCHOOLS AND BEYOND - FELIKS, TANS; NALLEY, HILDA M.; BHAE, JOHN (Academic Journal of Educational Sciences, 2023)
In this article, we argue that our students at any level, that is, from primary to tertiary institutions, must have good competences concerning critical thinking, creativity, collaboration, and communication, contemporarily known as 4Cs, namely, four major competences of the 21st Century, while they are in schools because they need those kinds of competences to succeed beyond those educational institutions. It is, therefore, crucial for our teachers, including lecturers, to always train their students in such a way that their mastery of those crucial competences is excellent when they are in schools in accordance with their levels of formal education. It is believed that having great competences as such in schools helps the students, among other things, successfully solve any problems they face when they live their real lives in their society after their formal schooling. In other words, those who fail in their real lives after formal schooling are those who have poor competences in relation to critical thinking, creativity, collaboration, and communication. So, making sure that our students have excellent competences on critical thinking, creativity, collaboration, and communication, when they are in schools, is necessary for them to succeed in their lives after their formal schooling.